Analysis of molten pool dynamics and surface smoothing time scale in laser polishing alloy materials. (June 2023) - Zhao, Shuang; Wang, Du; Liu, Jie; Yu, Mingjie; Yan, Ruopeng; Cui, Enkang; Liu, Sheng; Lei, Cheng
Highlights: The concept of surface smoothing time scale (SSTS) is proposed for the first time to calculate the process window of laser polishing. For Ti6 Al4 V and other metallic materials with a similar dynamic viscosity, the value of SSTS is hundred microseconds level. There is only one SSTS corresponding to an optimal laser-material interaction duration for a certain laser power density because of Marangoni effect. Experiments verified that the optimal combination of processing parameters can be found through the SSTS theory. Abstract: Laser polishing (LP) is a promising technology for improving surface quality, while the understanding of mechanism of the material redistribution dynamics in LP process remains incomplete. In this study, from the aspect of molten pool dynamics, we demonstrate that there is only one optimal laser-material interaction time for surface smoothing, which is defined as the surface smoothing time scale (SSTS). Through the multi-physics model and experimental research, we found that the typical SSTS value for alloy materials ranges from tens to hundreds of microseconds, which mainly depends on liquid phase viscosity of the material determined by the temporal and spatial variations of temperature field in the LP process. The evolution of molten pool flowing and surface roughness over time under non-uniform temperature field caused by different processing parameters, such as laser fluence and power density, are analyzed in detail. We found that the mechanism of existence of SSTS lies in the Marangoni effect caused by non-uniform temperature field. The Marangoni effect shortens the SSTS in the initial process, and it is also the main mechanism for boundary bulging when the radiation time exceeds the SSTS. Finally, we designed a series of experiments and found a fluctuation of the roughness with the processing parameters such as scanning speed, which can be well explained according to the SSTS theory. This study can provide a theoretical basis for acquiring the process window of LP.